A política educacional paulista e o processo de municipalização - 1995-2008: gerenciamento de resultados e patrimonialismo - Mello, Claudia Carnevskis de (Universidade Federal de São Carlos, 2010)
We analyzed in our study the changes in patterns of management of public systems of Basic School education reform proposed by the state of São Paulo. The proposed change has led, among other actions, the decentralization of education in primary schools managed by the state government in the management of the Governor Mário Covas. In his first administration, from 1995 to 1998, Covas put into running a series of measures and projects, which had continued in subsequent governments. Selected, from the analysis of these measures over the years and through interviews with municipal managers, the expectations and actual results of the municipalities that signed the covenant in charge of decentralization of its schools. It might be noted that changes in management patterns were based on the concept of results management, whose main characteristics are streamlining, decentralization, and evaluation of the system in line with the Strategic Plan of the State Apparatus. The enforcement of laws that permitted the structuring, establishment of goals and evaluation of public education systems made possible the implementation of a tariff reduction of economic and administrative activities without, in compensation, to settle municipal educational systems with permanent structures, with clear rules and objective, hierarchies and positions established. This caused much of the decisions being made off the cuff and that adjustments were made in each case. Seems to have been, in most cases, the concern to establish a body of officials and permanent rules allowing actions patrimonial character and can cripple the effectiveness of popular participation in the management of public schools.
Keywords: Política e educação; Reforma do ensino; Descentralização administrativa; Municipalização do ensino; Patrimonialismo; Mudanças dos padrões de gestão; Estado de São Paulo; Brotas; Embu das Artes; Peruíbe; Praia Grande; Juquitiba; Education reform; Decentralization; Municipalization of school; Patrimonialism; Changes in patterns of management; CIENCIAS HUMANAS::EDUCACAO